Poplar transformation with variable explant sources to maximize transformation efficiency - Haiwei Lu; Sara Jawdy; Jin-Gui Chen; Xiaohan Yang; Udaya C. Kalluri (Scientific Reports)
Abstract For decades, Agrobacterium tumefaciens-mediated plant transformation has played an integral role in advancing fundamental and applied plant biology. The recent omnipresent emergence of synthetic biology, which relies on plant transformation to manipulate plant DNA and gene expression for novel product biosynthesis, has further propelled basic as well as applied interests in plant transformation technologies. The strong demand for a faster design-build-test-learn cycle, the essence of synthetic biology, is, however, still ill-matched with the long-standing issues of high tissue culture recalcitrance and low transformation efficiency of a wide range of plant species especially food, fiber and energy crops. To maximize the utility of plant material and improve the transformation productivity per unit plant form, we studied the regeneration and transformation efficiency of different types of explants, including leaf, stem, petiole, and root from Populus, a woody perennial bioenergy crop. Our results show that root explants, in addition to the above-ground tissues, have considerable regeneration capacity and amenability to A. tumefaciens and, the resulting transformants have largely comparable morphology, reporter gene expression, and transcriptome profile, independent of the explant source tissue. Transcriptome analyses mapped to regeneration stages and transformation efficiencies further revealed the expression of the auxin and cytokinin signaling and various developmental pathway genes in leaf and root explants undergoing early organogenesis. We further report high-potential candidate genes that may potentially be associated with higher regeneration and transformation efficiency. Overall, our study shows that explants from above- and belowground organs of a Populus plant are suitable for genetic transformation and tissue culture regeneration, and together with the underlying transcriptome data open new routes to maximize plant explant utilization, stable transformation productivity, and plant transformation efficiency.